Pembuatan Pompa Air Tenaga Surya untuk Irigasi Persawahan Bagi Masyarakat Desa Mlaras Sumobito Jombang - Wardana, Humaidillah Kurniadi; Minto; Ummah, Imamatul (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2023)
The need for water for irrigating rice fields in Mlarasa Sumobito Jombang village is needed throughout the year to prevent drought or crop failure. The problem faced by partners is the increasingly high price of fuel to turn on the diesel pumps used to irrigate water from rivers or water sources (wells) to the rice fields. Solar energy is a renewable energy source that can be utilized, created, and widely available in Indonesia. Solar panels are used to convert solar energy into electrical energy. The purpose of this community service activity is to provide training socialization on the use of solar panels as a source of electrical energy used to turn on water pumps equipped with an IoT monitoring system to facilitate supervision so that they can save other energy sources. The designed solar panel pump can irrigate rice fields continuously for 8 hours per day with a pump output discharge of Â± 400 liters per minute with a pump power of 850 watts with a duration of battery capacity of 76 hours. The socialization of the training was divided into 3 sessions, namely the opening, the core contained knowledge about irrigation systems, solar panels, making solar water pumps, maintenance (maintenance), and finally the process of testing solar water pumps in farmers' fields. The solar water pump that has been made is able to answer all the needs of Mlaras village farmers in reducing the use of diesel pumps with fuel.